ACADEMIC SUPERVISION AND TEACHER REFLECTION: A CASE STUDY OF PEDAGOGICAL DEVELOPMENT AT SMA NEGERI 3 BOYOLALI - Elok Nur Faiqoh; Nurkolis; Sumarno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates the role of academic supervision in enhancing the pedagogical competence of teachers at SMA Negeri 3 Boyolali. Using a qualitative case study approach, the research explores the systematic planning, collaborative implementation, and evaluation of academic supervision, as well as its impact on teacher reflection and development. The findings indicate that academic supervision, conducted through class observations, reflective discussions, and constructive feedback, significantly contributes to teachers' pedagogical competence. Teachers' active engagement in reflective practices following supervision helps improve lesson planning, classroom management, and teaching methods. The study also highlights the importance of ongoing professional development through training and workshops as part of the supervision follow-up. Despite its success, the research acknowledges limitations such as time constraints and scheduling conflicts, which occasionally hinder the effectiveness of supervision. This study provides valuable insights for schools seeking to enhance teacher quality through effective academic supervision.